The influence of environmental variables and dispersal abilities on distribution of aquatic macroinvertebrate larvae in isolated spring fens - Rádková, Vanda; Horsák, Michal, 1975-; Masarykova univerzita. Ústav botaniky a zoologie (2016)
Cílem dizertační práce je přispět k hlubšímu poznání mechanismů určujících složení metaspolečenstev, jednomu z ústředních témat současné ekologie. Moderní výzkum se nejčastěji zaměřuje na určení vlivu lokálních podmínek prostředí (tzn. “species sorting”) a prostorových procesů, které jsou výsledkem rozdílných schopností šíření jednotlivých druhů (tzn. neutrální hypotéza). Tento úkol je mnohdy velmi obtížný kvůli složitosti vztahů mezi společenstvy a jejich prostředím, nemožnosti oddělit často nevyhnutelně spjaté vlivy prostředí a prostoru a neznalost podrobných vlastností druhů. Prameništní slatiniště představují ideální modelový systém pro testování těchto ekologických otázek a teorií. Tyto biotopy poskytují útočiště rozmanitému a druhově bohatému společenstvu s vysokým podílem druhů, které jsou na toto specifické prostředí vázané.
This thesis aims to contribute to a deeper understanding of structuring mechanisms driving the composition of metacommunities, one of the central issues of contemporary ecology. The modern research focuses mainly on disentangling the roles of local environmental conditions (i.e. species sorting) and spatial processes resulting from different dispersal abilities of species (i.e. neutral hypothesis). The task is often challenging due to a complexity of interconnected relationships between communities and environment, inability to separate necessarily dependent effects of the environment and space and/or lack of information about detailed species traits. Spring fens represent the ideal model system for testing such ecological topics and theories. These habitats host diverse and species-rich communities with high proportion of species adapted to this specific environment.
Vedoucí práce: Michal Horsák
Dizertace (Ph.D.)--Masarykova univerzita, Přírodovědecká fakulta, 2016
Keywords: larvy; prameniště; slatiny; vodní bezobratlí; vodní ekosystémy; aquatic invertebrates; fens; larvas; spring area; water ecosystems; disertace; dissertations